Fibrous copper-based powder-containing powder metallurgy friction material for high-power-density wet clutch

By adding fibrous copper powder to the wet clutch friction material, the problem of low oil storage and permeability in the material in a wet environment is solved, the hardness and tensile strength of the friction plate are improved, the stability of the friction coefficient and the low wear rate are ensured, and the service life of the friction plate is extended.

CN119897456APending Publication Date: 2025-04-29CENT SOUTH UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311394024.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing wet clutch friction materials have low oil storage and permeability in wet environments, and the oil film cannot be guaranteed, which affects the reliability and life of the friction plate.

Method used

Fibrous copper powder is added to the copper-based powder metallurgical friction material. By designing the ratio of fibrous copper powder to electrolytic copper powder, and combining suitable friction components and lubricating components, the hardness, tensile strength and porosity of the material are improved.

Benefits of technology

It significantly improves the hardness, compressive strength and thermal conductivity of copper-based powder metallurgical friction sheets, ensures the stable friction coefficient and low wear rate in wet friction environments, and extends the service life of the friction sheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897456A_ABST
    Figure CN119897456A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength and high-open porosity powder metallurgy friction material for a high-power-density wet clutch. The friction material is prepared from, by mass, 50%-75% of copper powder, 3%-8% of zinc powder, 2%-7% of tin powder, 7%-15% of crystalline flake graphite, 7%-15% of artificial graphite, 1%-2% of silicon dioxide, 3%-6% of zirconium dioxide and 1%-5% of nickel-plated molybdenum disulfide. The copper powder comprises fibrous copper powder, and the particle size distribution of the fibrous copper powder is as follows: 4-6vol% of copper powder with the particle size of less than 5 microns; 60-66vol% of copper powder with a particle size of 5-20 [mu] m; the particle size is greater than 20 [mu] m and less than or equal to 45 [mu] m: 31-35 vol%, and the particle size is greater than 45 [mu] m and less than or equal to 75 [mu] m: 1-3 vol%. The preparation method comprises a powder metallurgy method. The composition is reasonable in design, the preparation process is simple, and the obtained product is excellent in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical understanding of powder metallurgy friction materials, and in particular to a high-strength and high-open-porosity powder metallurgy friction material for a high-power-density wet clutch. Background Art

[0002] The clutch is a traditional mechanical device, mainly used to control the connection and disconnection between the engine and the transmission system, and to achieve functions such as starting, speed change, and hovering. According to the mechanism of action, it can be divided into four types: electromagnetic clutch, magnetic powder clutch, friction clutch, and hydraulic clutch. According to the working conditions, it can be divided into two types: dry and wet clutch. Among them, the wet friction clutch transmits torque through the mechanical force generated by the rough peak contact between the friction pairs and the belt torque caused by the viscosity of the lubricating oil between the friction pairs. Due to its high torque and power output transmission capacity, good heat dissipation performance, stable working process, and high reliability, it has outstanding advantages in aerospace, aviation, navigation and other fields. In order to ensure the reliable and effective operation of the clutch, the ideal wet friction material should have the characteristics of good heat dissipation performance, low temperature rise, good stability, good anti-attenuation performance, low wear, and long life. This requires that the clutch friction material has high strength to resist wear, and also needs to have a certain amount of pores to increase the permeability of lubricating oil in the friction material and promote the formation and continuity of the oil film at the friction interface.

[0003] At present, the friction materials used in wet clutches mainly include resin-based friction materials, paper-based friction materials, carbon-based friction materials and powder metallurgy metal-based friction materials, etc. Among them, powder metallurgy metal-based friction materials are based on metal components, with appropriate friction components and lubricating components added. They have the advantages of high mechanical strength, good thermal conductivity, strong heat resistance, relatively high and stable friction coefficient, etc. Therefore, they are mostly used in transmission requirements with high speed, high load or special working conditions.

[0004] China's public patent CN111022532B discloses a clutch friction plate and its preparation method and clutch. The clutch friction material layer is composed of the following components: 15-30% ceramic fiber, 0.5-3% carbon nanotube, 10-30% phenolic resin, 0.1-1% brown corundum, 2-6% aluminum oxide, 1-5% zirconium silicate, 3-6% antimony sulfide, 2-18% calcium carbonate, 1-3% tungsten cobalt alloy powder, and 30-50% barium sulfate. The preparation method adopted is hot pressing. The friction plate belongs to the resin-based friction material for automobile clutch. The friction plate prepared has the advantages of high temperature resistance, wear resistance, low noise, stable friction braking torque, and environmental protection.

[0005] China's public patent CN113275554B discloses a copper-based powder metallurgy clutch friction plate for switch machine and its manufacturing method, which includes the following preparation steps: mixing raw materials, cold pressing on copper-plated steel core plate, pressurized sintering, furnace cooling, and blank machining; it contains the following ingredients: electrolytic copper powder, iron powder, tin powder, manganese powder, mullite, molybdenum disulfide, silicon dioxide, flake graphite, and artificial graphite. The material has excellent friction and wear performance, stable braking performance, high safety factor, green environmental protection, high cost performance, and excellent durability and reliability in high humidity (≥90%) environment and extreme temperature (-40℃~+70℃) environment.

[0006] China's public patent CN113153927B discloses a powder metallurgy friction material for aviation high power density wet clutch, the friction material is measured by volume percentage as follows: 35-55% copper, 1-5% tin, 4-6% silicon dioxide, 4-6% zirconium dioxide, 20-35% flake graphite, 5-15% granular graphite, 1-2% molybdenum disulfide. Its preparation process includes the following steps: batching, mixing, pressing and sintering. The prepared friction material has good high power density disconnection and connection service capability, meeting the disconnection and connection function of aviation high power density wet clutch.

[0007] From the above patent disclosures, it can be seen that the existing clutch friction plates use different material components to improve the service performance of the friction material. Among the above friction plates, the resin-based friction plates have a low friction power density during operation; the design process of the powder metallurgy metal-based friction material does not take into account the matching between the strength and porosity of the material, resulting in low oil storage rate and permeability of the friction material in a wet environment, and the oil film cannot be guaranteed, thus affecting the reliability and life of the friction plate. Summary of the invention

[0008] In view of the above problems, the purpose of the present invention is to provide a high-strength and high-open porosity powder metallurgy friction material for a high-power density wet clutch. In the field of copper-based powder metallurgy friction materials for wet clutches, fibrous copper powder is added to copper-based powder for the first time. By designing the ratio of fibrous copper powder to electrolytic copper powder, and matching appropriate friction components and lubricating components, a copper-based powder metallurgy friction material for a wet clutch with high hardness, high tensile strength, appropriate and stable friction coefficient, and low wear rate is obtained.

[0009] The present invention discloses a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder. The raw materials used include the following components in terms of mass percentage:

[0010] 50-75% copper powder, 3-8% zinc powder, 2-7% tin powder, 7-15% flake graphite, 7-15% artificial graphite, 1-2% silicon dioxide, 3-6% zirconium dioxide, 1-5% nickel-plated molybdenum disulfide; the fibrous copper powder includes fibrous copper powder with a particle size of 5-20 μm and fibrous copper powder with a particle size greater than 20 μm and less than or equal to 45 μm; the copper powder with a particle size of 5-20 μm accounts for 50-70% of the total volume of the fibrous copper powder, and the copper powder with a particle size greater than 20 μm and less than or equal to 45 μm accounts for 30-50% of the total volume of the fibrous copper powder. The powder particle size distribution is statistically obtained using a laser particle size analyzer.

[0011] As a preferred embodiment, the fibrous copper powder includes: copper powder with a particle size of less than 5 μm: 4 to 6 vol%; copper powder with a particle size of 5 to 20 μm: 50 to 60 vol%; copper powder with a particle size greater than 20 μm and less than or equal to 45 μm: 31 to 41 vol%, and copper powder with a particle size greater than 45 μm and less than or equal to 75 μm: 1 to 3 vol%.

[0012] As a preferred embodiment, the present invention provides a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, wherein the content of the fibrous copper powder in the copper powder is 25-100%.

[0013] As a preferred embodiment, the present invention provides a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, wherein the raw materials used include the following components by mass percentage:

[0014] 50-68% copper powder, 2-8% zinc powder, 3-6% tin powder, 8-13% flake graphite, 8-13% artificial graphite, 1-3% silicon dioxide, 4-6% zirconium dioxide, 1-4% nickel-plated molybdenum disulfide; the proportion of electrolytic copper powder in the copper powder is 0-75%, and the proportion of fibrous copper powder is 25-100%.

[0015] The nickel content in the nickel-plated molybdenum disulfide is 15-30wt% of the nickel-plated molybdenum disulfide.

[0016] The particle size of the zinc powder is ≤200 μm, preferably 50 to 100 μm;

[0017] The particle size of the tin powder is ≤200 μm, preferably 50 to 100 μm;

[0018] The particle size of the flake graphite is ≤300 μm, preferably 100 to 160 μm;

[0019] The particle size of artificial graphite is ≤500 μm, preferably 150-300 μm;

[0020] The particle size of silicon dioxide is ≤200 μm, preferably 50 to 100 μm;

[0021] The particle size of zirconium dioxide is ≤200 μm, preferably 50 to 100 μm;

[0022] The particle size of nickel-plated molybdenum disulfide is ≤200 μm, preferably 50-100 μm. As a further preferred embodiment, the present invention provides a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, wherein the raw materials used include the following components in terms of mass percentage:

[0023] 55-65% copper powder, 5-7% zinc powder, 4-6% tin powder, 10% flake graphite, 9-12% artificial graphite, 1-2.5% silicon dioxide, 5% zirconium dioxide, and 1-3% nickel-plated molybdenum disulfide; the proportion of electrolytic copper powder in the copper powder is 0-75%, and the proportion of fibrous copper powder is 25-100%.

[0024] As a further preferred embodiment, the present invention provides a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, wherein the electrolytic copper powder accounts for 25-75% of the copper powder, and further preferably for 35-60%, and of course 45-55% has a better effect.

[0025] As one of the best solutions, the present invention provides a powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, wherein the raw materials used include the following components in terms of mass percentage:

[0026] Copper powder 60%, zinc powder 6%, tin powder 5%, flake graphite 10%, artificial graphite 10%, silicon dioxide 2%, zirconium dioxide 5%, nickel-plated molybdenum disulfide 2%; the copper powder comprises 50% electrolytic copper powder and 50% fibrous copper powder.

[0027] Compared with the scheme of using pure electrolytic copper powder, the powder used in the present invention has good bonding performance with the components in the friction material, the physical properties and tribological properties of the prepared friction material are good, and it has a certain open porosity. The prepared friction material has higher hardness and compressive strength than other schemes, and the friction coefficient is more stable in a wet friction environment, and the wear rate is lower.

[0028] The present invention discloses a powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder, the preparation of which comprises the following steps:

[0029] (1) Weigh the above powders according to weight and pour them into a mixer.

[0030] (2) The mixed powder is placed in a corresponding mold and cold pressed under a hydraulic press.

[0031] (3) The green body is placed in a hot pressing sintering furnace for sintering.

[0032] (4) Cool to below 100°C and take out, keeping the pressure unchanged during the cooling process.

[0033] Furthermore, in step (1), all the powders are first mixed manually and preliminarily mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh screen to prevent agglomeration. After the pre-mixing is completed, the powder is put into a three-dimensional mixer for mixing for 6-8 hours.

[0034] Furthermore, in step (2), the pressing pressure is 350 to 650 MPa, preferably 390 to 410 MPa, and the holding time is 2 to 8 s.

[0035] Furthermore, in step (3), the sintering temperature is 650-870°C, preferably 730-750°C, the holding time is 3-5h, preferably 220-260min, the sintering pressure is 2-6MPa, preferably 3-4MPa, and the sintering process is carried out in a hydrogen atmosphere.

[0036] The invention discloses a powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder, the density of which is 4 to 5.25 g / cm 3 , open porosity is 18-22%, tensile strength is 25-50 MPa, hardness (HBW) is 15-30, and thermal conductivity is 8-12 W / (m·K).

[0037] The present invention obtains for the first time a product with a porosity of 18-22%, a tensile strength of 31-39 MPa, a hardness (HBW) of 16.5-20.5, and a thermal conductivity of 9.4-11.4 W / (m·K). When the friction performance of the product is tested in the MM-3000 friction test engine oil environment, the friction coefficient is 0.097-0.13, and the wear rate is 5.1-6.8x10 -5 mm 3 / J.

[0038] When the present invention adopts MM-3000 friction test to detect friction performance in the engine oil environment, the condition parameters are that the friction speed is 6000rpm and the friction pressure is 2MPa.

[0039] The above technical solution of the present invention has the following advantages:

[0040] The friction material of the present invention is prepared by adding an appropriate amount of fibrous copper powder of different particle sizes to electrolytic copper powder, which effectively solves the problems that the electrolytic copper powder is easily broken during dispersion and pressing, and has poor bonding performance with the matrix during sintering, and significantly improves the matrix strength of the copper-based powder metallurgy friction plate; in addition, the characteristics of the surface voids of the fibrous copper powder enable the friction material to have a certain porosity, and the friction plate has a strong oil storage capacity and a high permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a friction coefficient diagram of the friction material obtained in Example 1 of the present invention;

[0042] Figure 2 This is a friction coefficient diagram of the friction material obtained in Example 2 of the present invention;

[0043] Figure 3 This is a friction coefficient diagram of the friction material obtained in Example 3 of the present invention;

[0044] Figure 4 This is a friction coefficient diagram of the friction material obtained in Example 4 of the present invention;

[0045] Figure 5 This is a friction coefficient diagram of the friction material obtained in Comparative Example 1 of the present invention;

[0046] Figure 6 This is a friction coefficient diagram of the friction material obtained in Example 5 of the present invention. DETAILED DESCRIPTION

[0047] In the embodiments and comparative examples of the present invention, when the friction performance is tested in the MM-3000 friction test engine oil environment, the condition parameters are a friction speed of 6000 rpm and a friction pressure of 2 MPa.

[0048] Embodiment 1:

[0049] In Example 1, the particle size of the electrolytic copper powder is ≤100 μm, and it is dendritic; the purity is greater than or equal to 99%.

[0050] In Example 1, among the fibrous copper powder, the copper powder with a particle size of less than 5 μm: 6.28 vol%; the copper powder with a particle size of 5 to 20 μm: 53.41 vol%; the copper powder with a particle size greater than 20 μm and less than or equal to 45 μm: 37.36 vol%; the copper powder with a particle size greater than 45 μm and less than or equal to 75 μm: 2.95 vol%. The purity is greater than or equal to 99%;

[0051] The particle size of zinc powder, tin powder, silicon dioxide, zirconium dioxide, and nickel-plated molybdenum disulfide is ≤200 μm, flake graphite is ≤300 μm, and artificial graphite is ≤500 μm. The mass percentage of nickel in the nickel-plated molybdenum disulfide is 18%.

[0052] The brake pad material prepared in this embodiment contains the following ingredients: 60% copper powder (50% electrolytic copper powder and 50% fibrous copper powder), 6% zinc powder, 5% tin powder, 10% flake graphite, 10% artificial graphite, 2% silicon dioxide, 5% zirconium dioxide, and 2% nickel-plated molybdenum disulfide. Each component is divided according to the mass percentage. First, all the powders are mixed manually and mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh screen to prevent agglomeration. After the premixing is completed, it is put into a three-dimensional mixer for mixing for 7 hours; the mixed powder is pressed into shape by a hydraulic press, the pressing pressure is 400MPa, and the pressure is maintained for 5s; the pressed powder is sintered in a hot pressing sintering furnace under hydrogen protection, the sintering temperature is 740°C, the pressure is maintained for 4h, and the sintering pressure is 3.5MPa.

[0053] The friction material prepared has a density of 4.68 g / cm3, a porosity of 20.8%, a tensile strength of 36.87 MPa, a hardness (HB) of 19.1, and a thermal conductivity of 10.4 W / (m·K). The friction material of this embodiment was tested in the MM-3000 friction test engine oil environment. The friction curve of the friction material is stable, the friction coefficient is 0.103, and the wear rate is 5.1x10 -5 mm 3 / J.

[0054] Example 2

[0055] In Example 2, the fibrous copper powder and electrolytic copper powder used are the same as those in Example 1;

[0056] The zinc powder, tin powder, flake graphite, artificial graphite, silicon dioxide, zirconium dioxide, and nickel-plated molybdenum disulfide used are all the same as those in Example 1;

[0057] The brake pad prepared in this embodiment comprises the following components:

[0058] 60% copper powder (75% electrolytic copper powder, 25% fibrous copper powder), 6% zinc powder, 5% tin powder, 10% flake graphite, 10% artificial graphite, 2% silicon dioxide, 5% zirconium dioxide, 2% nickel-plated molybdenum disulfide, each component is divided according to mass percentage. First, all powders are mixed manually and initially mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh screen to prevent agglomeration. After premixing, it is put into a three-dimensional mixer for mixing for 7 hours; the mixed powder is pressed into shape by a hydraulic press, the pressing pressure is 400MPa, and the pressure is maintained for 5s; the pressed powder is sintered in a hot pressing sintering furnace under hydrogen protection, the sintering temperature is 740℃, the pressure is maintained for 4h, and the sintering pressure is 3.5MPa.

[0059] The friction plate material prepared has a density of 5.03 g / cm3, a porosity of 18.4%, a tensile strength of 31.12 MPa, a hardness (HB) of 16.5, and a thermal conductivity of 10.8 W / (m·K). The friction material of this embodiment was tested in the MM-3000 friction test oil environment. The friction curve of the friction material is stable, the friction coefficient is 0.096, and the wear rate is 6.8x10 -5 mm 3 / J.

[0060] Example 3

[0061] In Example 3, the fibrous copper powder and electrolytic copper powder used are the same as those in Example 1;

[0062] The zinc powder, tin powder, flake graphite, artificial graphite, silicon dioxide, zirconium dioxide, and nickel-plated molybdenum disulfide used are all the same as those in Example 1;

[0063] The brake pad prepared in this embodiment comprises the following components:

[0064] 60% copper powder (25% electrolytic copper powder and 75% fibrous copper powder), 6% zinc powder, 5% tin powder, 10% flake graphite, 10% artificial graphite, 2% silicon dioxide, 5% zirconium dioxide, 2% nickel-plated molybdenum disulfide, and each component is divided according to mass percentage. First, all powders are mixed manually and initially mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh screen to prevent agglomeration. After premixing, it is put into a three-dimensional mixer for mixing for 7 hours; the mixed powder is pressed into shape by a hydraulic press, the pressing pressure is 400MPa, and the pressure is maintained for 5s; the pressed powder is sintered in a hot pressing sintering furnace under hydrogen protection, the sintering temperature is 740℃, the pressure is maintained for 4h, and the sintering pressure is 3.5MPa.

[0065] The friction plate material prepared has a density of 4.62 g / cm3, a porosity of 21.4%, a tensile strength of 32.46 MPa, a hardness (HB) of 17.4, and a thermal conductivity of 9.2 W / (m·K). The friction material of this embodiment was tested in the MM-3000 friction test oil environment. The friction curve of the friction material is stable, the friction coefficient is 0.094, and the wear rate is 6.9x10 -5 mm 3 / J.

[0066] Example 4

[0067] In Example 4, the fibrous copper powder and electrolytic copper powder used are the same as those in Example 1;

[0068] The zinc powder, tin powder, flake graphite, artificial graphite, silicon dioxide, zirconium dioxide, and nickel-plated molybdenum disulfide used are all the same as those in Example 1;

[0069] The brake pad prepared in this embodiment comprises the following components:

[0070] 60% copper powder (including 0% electrolytic copper powder and 100% fibrous copper powder), 6% zinc powder, 5% tin powder, 10% flake graphite, 10% artificial graphite, 2% silicon dioxide, 5% zirconium dioxide, 2% nickel-plated molybdenum disulfide, and each component is divided according to mass percentage. First, all powders are mixed manually and initially mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh screen to prevent agglomeration. After premixing, it is put into a three-dimensional mixer for mixing for 7 hours; the mixed powder is pressed into shape by a hydraulic press, with a pressing pressure of 400MPa and a holding pressure of 5s; the pressed powder is sintered in a hot pressing sintering furnace under hydrogen protection, with a sintering temperature of 740℃, a holding pressure of 4h, and a sintering pressure of 3.5MPa.

[0071] The friction plate material prepared has a density of 4.59 g / cm3, a porosity of 22.1%, a tensile strength of 30.45 MPa, a hardness (HB) of 16.9, and a thermal conductivity of 9.1 W / (m·K). The friction material of this embodiment was tested in the MM-3000 friction test engine oil environment. The friction curve of the friction material is stable, the friction coefficient is 0.097, and the wear rate is 7.9x10 -5 mm 3 / J.

[0072] Comparative Example 1

[0073] The copper powder used in Comparative Example 1 is electrolytic copper powder, and its amount is consistent with the amount of total copper powder in Example 1;

[0074] The zinc powder, tin powder, flake graphite, artificial graphite, silicon dioxide, zirconium dioxide, and nickel-plated molybdenum disulfide used are all the same as those in Example 1;

[0075] The brake pad material prepared in this comparative example comprises the following components:

[0076] Copper powder 60% (including electrolytic copper powder 100%, fibrous copper powder 0%), zinc powder 6%, tin powder 5%, flake graphite 10%, artificial graphite 10%, silicon dioxide 2%, zirconium dioxide 5%, nickel-plated molybdenum disulfide 2%, and each component is divided according to mass percentage.

[0077] First, all the powders were mixed manually and mixed in a drum mixer for 30 minutes, and then the mixed powders were screened with an 80-mesh screen to prevent agglomeration. After premixing, they were put into a three-dimensional mixer for 7 hours; the mixed powders were pressed into shape using a hydraulic press with a pressing pressure of 400 MPa; the pressed powders were sintered in a hot pressing sintering furnace under hydrogen protection with a sintering temperature of 740°C, a holding time of 4 hours, and a sintering pressure of 3.5 MPa.

[0078] The friction plate material prepared has a density of 5.42 g / cm3, a porosity of 15%, a tensile strength of 25 MPa, a hardness (HB) of 13.8, and a thermal conductivity of 7.2%. The friction material of this embodiment was tested under the engine oil environment using the MM-3000 friction tester. The friction curve of the friction material was stable, the friction coefficient was 0.091, and the wear rate was 8.2x10 -5 mm 3 / J.

[0079] Example 5

[0080] Other conditions are consistent with those in Example 1, except that the fibrous copper powder is composed of fibrous copper powder with a particle size of 5 to 20 μm and fibrous copper powder with a particle size greater than 20 μm and less than or equal to 45 μm, wherein the fibrous copper powder with a particle size of 5 to 20 μm: 50 vol%; the particle size greater than 20 μm and less than or equal to 45 μm: 50 vol%; the prepared friction plate material has a density of 5.20 g / cm3, a porosity of 18.2%, a tensile strength of 38.24 MPa, a hardness (HB) of 20.4, and a thermal conductivity of 11.2 W / (m·K). The friction material of this comparative example was tested in the MM-3000 friction test engine oil environment. The friction curve of the friction material was stable, the friction coefficient was 0.13, and the wear rate was 5.9x10 -5 mm 3 / J.

[0081] By comparing Example 1 and Example 5 of the present invention, it can be seen that the particle size matching of the fibrous copper powder will have a relatively large impact on the density, friction coefficient and wear rate of the final product. Among them, the wear rate of the product prepared by using two fibrous copper powders with different particle sizes will increase by 12 to 16% compared with the wear rate of the product prepared by using four fibrous copper powders with different particle sizes.

[0082] By comparing Example 1 of the present invention with Examples 2-4, it can be seen that the ratio of the electrolytic copper powder to the fibrous copper powder has a crucial influence on the final performance of the product.

Claims

1. A powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder, characterized in that: The raw materials used include the following components by mass percentage: Copper powder 50-75%, zinc powder 3-8%, tin powder 2-7%, flake graphite 7-15%, artificial graphite 7-15%, silicon dioxide 1-2%, zirconium dioxide 3-6%, nickel-plated molybdenum disulfide 1-5%; 50-75% copper powder, 3-8% zinc powder, 2-7% tin powder, 7-15% flake graphite, 7-15% artificial graphite, 1-2% silicon dioxide, 3-6% zirconium dioxide, and 1-5% nickel-plated molybdenum disulfide; the fibrous copper powder includes fibrous copper powder with a particle size of 5-20 μm and fibrous copper powder with a particle size greater than 20 μm and less than or equal to 45 μm; the copper powder with a particle size of 5-20 μm accounts for 50-70% of the total volume of the fibrous copper powder, and the copper powder with a particle size greater than 20 μm and less than or equal to 45 μm accounts for 30-50% of the total volume of the fibrous copper powder.

2. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 1, characterized in that: The content of fibrous copper powder in the copper powder is 25-100%; the fibrous copper powder includes: copper powder with a particle size of less than 5 μm: 4-6 vol%; copper powder with a particle size of 5-20 μm: 50-60 vol%; copper powder with a particle size greater than 20 μm and less than or equal to 45 μm: 31-41 vol%, and copper powder with a particle size greater than 45 μm and less than or equal to 75 μm: 1-3 vol%.

3. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 1, characterized in that: The raw materials used include the following components by mass percentage: 50-68% copper powder, 2-8% zinc powder, 3-6% tin powder, 8-13% flake graphite, 8-13% artificial graphite, 1-3% silicon dioxide, 4-6% zirconium dioxide, 1-4% nickel-plated molybdenum disulfide; the proportion of electrolytic copper powder in the copper powder is 0-75%, and the proportion of fibrous copper powder is 25-100%.

4. The powder metallurgy friction material for a high power density wet clutch containing fibrous copper-based powder according to claim 1, characterized in that: The nickel content of the nickel-plated molybdenum disulfide is 15-30wt% of the nickel-plated molybdenum disulfide; The particle size of the zinc powder is ≤200 μm, preferably 50 to 100 μm; The particle size of the tin powder is ≤200 μm, preferably 50 to 100 μm; The particle size of the flake graphite is ≤300 μm, preferably 100 to 160 μm; The particle size of artificial graphite is ≤500 μm, preferably 150-300 μm; The particle size of silicon dioxide is ≤200 μm, preferably 50 to 100 μm; The particle size of zirconium dioxide is ≤200 μm, preferably 50 to 100 μm; The particle size of the nickel-plated molybdenum disulfide is ≤ 200 μm, preferably 50 to 100 μm.

5. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 3, characterized in that: The raw materials used include the following components by mass percentage: 55-65% copper powder, 5-7% zinc powder, 4-6% tin powder, 10% flake graphite, 9-12% artificial graphite, 1-2.5% silicon dioxide, 5% zirconium dioxide, and 1-3% nickel-plated molybdenum disulfide; the proportion of electrolytic copper powder in the copper powder is 0-75%, and the proportion of fibrous copper powder is 25-100%.

6. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 5, characterized in that: The proportion of electrolytic copper powder in the copper powder is 25-75%, and more preferably 35-60%.

7. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 6, characterized in that: The raw materials used include the following components by mass percentage: Copper powder 60%, zinc powder 6%, tin powder 5%, flake graphite 10%, artificial graphite 10%, silicon dioxide 2%, zirconium dioxide 5%, nickel-plated molybdenum disulfide 2%; the copper powder comprises 50% electrolytic copper powder and 50% fibrous copper powder.

8. A powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to any one of claims 1 to 7, characterized in that: It is prepared by the following steps: (1) Weighing the raw material powders according to the set ratio, pouring them into a mixer, and mixing them evenly to obtain a mixed powder; (2) placing the mixed powder into a mold and cold pressing it under a hydraulic press; the pressing pressure is 350-650 MPa; (3) placing the green body in a hot pressing sintering furnace for sintering; the sintering temperature is 650-870°C, and the holding time is 3-5h; (4) Cool to below 100°C and take out, keeping the pressure unchanged during the cooling process.

9. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 8, characterized in that: In step (1), all powders are first mixed manually and preliminarily mixed in a drum mixer for 30 minutes, and then the mixed powder is passed through an 80-mesh sieve to prevent agglomeration; after the premixing is completed, the powder is put into a three-dimensional mixer for mixing for 6-8 hours; In step (2), the pressing pressure is 390-410 MPa, and the holding time is 2-8 s; In step (3), the sintering temperature is 730-750° C., the holding time is 3-5 hours, the sintering pressure is 2-6 MPa, and the sintering process is carried out in a hydrogen atmosphere.

10. The powder metallurgy friction material for a wet clutch with high power density containing fibrous copper-based powder according to claim 8, characterized in that: The density of the obtained product is 4-5g / cm 3 , porosity is 18-22%, tensile strength is 25-50 MPa, hardness HBW is 15-30, and thermal conductivity is 8-12 W / (m·K).

Citation Information

Patent Citations

  • A clutch friction plate, its manufacturing method, and a clutch

    CN111022532B

  • A powder metallurgical friction plate material for high power density wet clutches in aviation

    CN113153927B

  • A copper-based powder metallurgy clutch friction plate for a switch machine and its manufacturing method

    CN113275554B

  • Ship wet friction material and preparation method thereof

    CN102094134A

  • Steel-backing non-electroplating copper alloy based friction material and preparation method and application for friction piece

    CN105436496A